2015
DOI: 10.3892/br.2015.533
|View full text |Cite
|
Sign up to set email alerts
|

V-PYRRO/NO downregulates mRNA expression levels of leukotriene C4 synthase during hepatic ischemia reperfusion injury in rats via inhibition of the nuclear factor-κB activation pathway

Abstract: The aim of the present study was to explore the mechanism underlying the effects of a selective liver nitric oxide (NO) donor, O-vinyl1-(pyrrolidin-1-yl)-diazen-1-ium-1,2-diolate (V-PYRRO/NO), on the gene expression of leukotriene C4 synthase (LTC4S) during hepatic ischemia/reperfusion (I/R). Adult male Sprague-Dawley rats were divided into 3 groups: Sham (control), I/R and V-PYRRO/NO + I/R groups. The liver was subjected to 1 h of partial hepatic ischemia followed by 5 h of reperfusion, saline or V-PYRRO/NO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, this is reversed by V-PYRRO/NO, which acts as an NO donor. Hong et al [ 20 ] also found that another NO donor, sodium nitroprusside, could down-regulate the mRNA expression of LTC4S by inhibiting nuclear factor-kappa B (NF-κB) activation in an NF-κB α inhibitor-independent manner by detecting the protein levels of NF-κB p65 and p50 in the nuclear extracts using Western Blot.…”
Section: Different Roles Of No During Hirimentioning
confidence: 99%
“…However, this is reversed by V-PYRRO/NO, which acts as an NO donor. Hong et al [ 20 ] also found that another NO donor, sodium nitroprusside, could down-regulate the mRNA expression of LTC4S by inhibiting nuclear factor-kappa B (NF-κB) activation in an NF-κB α inhibitor-independent manner by detecting the protein levels of NF-κB p65 and p50 in the nuclear extracts using Western Blot.…”
Section: Different Roles Of No During Hirimentioning
confidence: 99%